2009
DOI: 10.1134/s1075701509070095
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of nyerereite and gregoryite from natrocarbonatites of Oldoinyo Lengai volcano, Tanzania

Abstract: phenocrysts and also occur in the groundmass of natrocarbonatite. The minor minerals are fluorite and sylvite, which compose the groundmass of natrocarbonatites. Accessory minerals are alabandite, magnetite, fluorapatite, monticellite, neighborite, sphalerite, galena, pyrrhotite, rasvumite, niocalite-cuspidine solid solution, and khanneshite, a carbonate of the burbankite group

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
53
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 21 publications
8
53
0
Order By: Relevance
“…This mineral assemblage is similar to other inclusions observed in gregoryite crystals (Mitchell 2006). The outer rims of the gregoryites are generally more sodium rich compared to the cores (Peterson 1990;Zaitsev et al 2008). Fig.…”
Section: Petrography Of Natrocarbonatitic Lavassupporting
confidence: 62%
See 3 more Smart Citations
“…This mineral assemblage is similar to other inclusions observed in gregoryite crystals (Mitchell 2006). The outer rims of the gregoryites are generally more sodium rich compared to the cores (Peterson 1990;Zaitsev et al 2008). Fig.…”
Section: Petrography Of Natrocarbonatitic Lavassupporting
confidence: 62%
“…In a recent paper, Zaitsev et al (2008) reported that some samples of natrocarbonatite from Oldoinyo Lengai display distinctively different gregoryite compositions (i.e., lower Na 2 O and higher CaO content) than found in most lavas from the volcano. The sample (OL-3a in Zaitsev et al 2008) is fast quenched lapilli from the 1992 eruption of Oldoinyo Lengai.…”
Section: Discussion Phase Equilibria: Implications For Magma Ascentmentioning
confidence: 99%
See 2 more Smart Citations
“…1). The volcano is famous for its unique low-temperature and lowviscosity natrocarbonatites (Keller and Krafft, 1990;Peterson, 1990;Zaitsev et al, 2009). However, the 3000 m high cone is made up of predominantly silicate lavas and pyroclastics (Donaldson et al, 1987;Dawson et al, 1989;Dawson, 1998;Klaudius and Keller, 2006).…”
Section: Introductionmentioning
confidence: 99%